(untitled) - Gillespie, Thomas (Warrendale, PA, 1992)
The first book providing comprehensive coverage of vehicle dynamics in a single volume, Fundamentals of Vehicle Dynamics provides a foundation of engineering principles and analytical methods to explain the performance of an automotive vehicle, with chapters focusing on: acceleration performance; braking performance; aerodynamics and rolling resistance; ride; tires; steady-state cornering; suspensions; steering systems; and rollover.
Keywords: Motor vehicles,Động cơ xe; Dynamics,Động lực học